Composite polymer film as well as preparation method and application thereof

By using ultrasonic spraying technology on alkaline electrolytic hydrogen production diaphragm to form polyvinyl alcohol film and perform cross-linking reactions, the problem of insufficient gas barrier properties of the existing membrane is solved, and higher gas barrier properties and electrolyte transmission performance are achieved, supporting the development of alkaline electrolytic hydrogen production technology.

CN119751951APending Publication Date: 2025-04-04HUANENG CLEAN ENERGY RES INST +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411894331.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-20
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

The gas barrier of the existing separators used for hydrogen production by alkaline electrolytic water is insufficient, resulting in safety hazards in the electrolytic cell system and it is difficult to meet the needs of industrial development.

Method used

Ultrasonic spraying technology is used to form a polyvinyl alcohol film on the polymer base film, and cross-linking reaction is carried out in a closed environment to form a modified layer, thereby improving the gas barrier properties of the composite polymer separator.

Benefits of technology

The gas barrier properties, electrolyte transmission performance and mechanical strength of the composite polymer separator are significantly improved, the service life of the separator is extended, and the efficiency of hydrogen production by electrolyzing water is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005201334040000091
    Figure BDA0005201334040000091
  • Figure BDA0005201334040000101
    Figure BDA0005201334040000101
Patent Text Reader

Abstract

The invention provides a composite polymer film as well as a preparation method and application thereof. The preparation method comprises the following steps: preparing polyvinyl alcohol into a polyvinyl alcohol solution; spraying a polyvinyl alcohol solution on the surface of one side of the polymer base membrane by adopting an ultrasonic spraying mode, and drying to obtain the polymer base membrane loaded with a polyvinyl alcohol membrane; preparing a cross-linking agent into a cross-linking agent solution; placing a cross-linking agent solution and the polymer base membrane loaded with the polyvinyl alcohol membrane in a closed environment, so that the cross-linking agent is diffused and is in contact with the polyvinyl alcohol membrane; and through a cross-linking reaction, the cross-linking agent and the polyvinyl alcohol membrane form a modified layer, so that the composite polymer diaphragm is obtained. According to the preparation method, the polyvinyl alcohol membrane is formed on the polymer base membrane through an ultrasonic spraying technology, then diffusion and in-situ cross-linking reaction are carried out in a closed environment, and an ultrathin selective surface layer is formed on the surface of one side of the polymer base membrane, so that the overall aperture characteristic of the obtained composite polymer diaphragm is effectively optimized, and the gas barrier property of the composite polymer diaphragm is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of hydrogen production by alkaline water electrolysis, and in particular to a composite polymer membrane, a preparation method and application thereof. Background Art

[0002] As a highly potential energy carrier and raw material, hydrogen energy can be applied to energy, transportation, chemical industry, steel and other fields. Using renewable energy such as solar energy, wind energy, and hydropower to electrolyze water to produce hydrogen is an efficient hydrogen production strategy with zero carbon emissions. Compared with proton exchange membrane (PEM) water electrolysis, anion exchange membrane (AEM) water electrolysis and solid oxide water electrolysis (SOE), alkaline water electrolysis (AWE) has the advantages of low manufacturing cost, high technical reliability and good stability. It is considered to be the only renewable energy water electrolysis hydrogen production technology solution that can achieve large-scale and low-cost.

[0003] In the alkaline water electrolysis hydrogen production process, the diaphragm, as the core material of the alkaline electrolyzer, plays the role of transmitting electrolyte and blocking hydrogen and oxygen gases. Therefore, the performance of the diaphragm has an important impact on the efficiency and safety of the electrolyzer. At present, the woven polyphenylene sulfide diaphragm (i.e., PPS diaphragm) with excellent heat resistance, high mechanical strength, and excellent electrical properties has been widely used in industrial alkaline electrolyzers, occupying a large market share.

[0004] However, in actual applications, it was found that since the pore structure in the PPS diaphragm is mainly produced by the woven structure and has a micron-level pore size, the gas barrier property is poor (bubble point pressure ≤ 0.02 Bar), which poses certain safety hazards to the electrolyzer system and is difficult to meet the needs of industrial development, such as renewable energy coupled with water electrolysis to produce hydrogen and high-pressure water electrolysis to produce hydrogen application scenarios.

[0005] Based on this, how to provide a preparation method for preparing a composite polymer membrane with high gas barrier properties, so that the obtained polymer membrane can support the development of alkaline water electrolysis hydrogen production technology and the upgrading of equipment, is one of the important technical problems that need to be solved in this field. Summary of the invention

[0006] The main purpose of the present invention is to provide a composite polymer membrane, a preparation method and application thereof, so as to solve the problem of insufficient gas barrier properties of the diaphragm used in the alkaline electrolysis of water to produce hydrogen in the prior art.

[0007] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a method for preparing a composite polymer diaphragm, comprising: step S1, preparing polyvinyl alcohol into a polyvinyl alcohol solution with a mass concentration of 0.01wt.% to 5.00wt.%; step S2, spraying the polyvinyl alcohol solution on one side surface of a polymer base film by ultrasonic spraying, and obtaining a polymer base film loaded with a polyvinyl alcohol film after drying; step S3, preparing a crosslinker into a crosslinker solution with a mass concentration of 0.1wt.% to 10.0wt.%; step S4, placing the crosslinker solution and the polymer base film loaded with a polyvinyl alcohol film in a closed environment to allow the crosslinker to diffuse and contact the polyvinyl alcohol film; after a crosslinking reaction, the crosslinker and the polyvinyl alcohol film form a modified layer, thereby obtaining a composite polymer diaphragm; the temperature of the closed environment is higher than the boiling point of the crosslinker, and the difference between the temperature of the closed environment and the boiling point of the crosslinker is 1°C to 100°C.

[0008] Furthermore, in step S1, the mass concentration of the polyvinyl alcohol solution is 0.1wt.% to 0.5wt.%; and / or, in step S3, the mass concentration of the cross-linking agent solution is 0.5wt.% to 2.5wt.%.

[0009] Further, in step S2, the number of spraying cycles of ultrasonic spraying is 0 to 1000 times, preferably 50 to 200 times; more preferably, the ultrasonic spraying speed of ultrasonic spraying is 0.1 mL / h to 2 mL / h, and the nozzle moving speed is 10 mm / s to 500 mm / s.

[0010] Furthermore, in step S2, the drying temperature is 30°C to 120°C, preferably 50°C to 100°C.

[0011] Furthermore, the cross-linking agent is selected from one or more of glutaraldehyde, glyoxal, formaldehyde, boric acid, dimethylol urea and trimethylol melamine, preferably glyoxal.

[0012] Further, in step S4, the temperature of the sealed environment is 50°C to 90°C, preferably 60°C to 80°C; preferably, the humidity of the sealed environment is 20%RH to 70%RH.

[0013] Furthermore, in step S4, the diffusion and cross-linking reaction time is 2 h to 48 h, preferably 12 h to 24 h.

[0014] Furthermore, the polymer-based membrane is selected from one or more of polyphenylene sulfide membrane, polytetrafluoroethylene membrane, polypropylene membrane and polysulfone membrane.

[0015] The second aspect of the present invention provides a composite polymer membrane, which is prepared by the above-mentioned composite polymer membrane preparation method; the composite polymer membrane includes a polymer base membrane and a modified layer arranged on the surface of at least one side of the polymer base membrane, and: the thickness of the polymer base membrane is 50μm to 600μm; and / or the thickness of the modified layer is 100nm to 8μm.

[0016] The third aspect of the present invention provides an application of the composite polymer membrane as an electrolytic cell membrane material in the field of hydrogen production by alkaline water electrolysis.

[0017] By applying the technical solution of the present invention, a polyvinyl alcohol film is uniformly formed on a polymer base film through ultrasonic spraying technology, and then diffusion and in-situ cross-linking reaction are carried out in a closed environment, forming an ultra-thin selective surface layer on one side of the polymer base film, thereby effectively optimizing the overall pore size characteristics of the obtained composite polymer diaphragm, and also improving the stability and mechanical strength of the composite diaphragm. The modified composite polymer diaphragm has more excellent gas barrier properties, electrolyte transport properties and mechanical strength, significantly improving the efficiency of hydrogen production by water electrolysis and the service life of the diaphragm, providing a high-performance diaphragm material for alkaline water electrolysis hydrogen production technology, and is conducive to promoting the development and application of clean energy. DETAILED DESCRIPTION

[0018] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.

[0019] As described in the background technology, the diaphragm used for hydrogen production by alkaline water electrolysis in the prior art has the problem of insufficient gas barrier properties. In order to solve the above technical problems, the first aspect of the present invention provides a method for preparing a composite polymer diaphragm, comprising: step S1, preparing polyvinyl alcohol into a polyvinyl alcohol solution with a mass concentration of 0.01wt.% to 5.00wt.%; step S2, spraying the polyvinyl alcohol solution on one side of the polymer base film by ultrasonic spraying, and obtaining a polymer base film loaded with polyvinyl alcohol film after drying; step S3, preparing a crosslinker into a crosslinker solution with a mass concentration of 0.1wt.% to 10.0wt.%; step S4, placing the crosslinker solution and the polymer base film loaded with polyvinyl alcohol film in a closed environment with a temperature of 50℃ to 90℃, so that the crosslinker diffuses and contacts with the polyvinyl alcohol film; after a crosslinking reaction, the crosslinker and the polyvinyl alcohol film form a modified layer, thereby obtaining a composite polymer diaphragm; the temperature of the closed environment is higher than the boiling point of the crosslinker, and the difference between the temperature of the closed environment and the boiling point of the crosslinker is 1℃ to 100℃.

[0020] The present invention firstly uses ultrasonic spraying technology to uniformly dry a polyvinyl alcohol solution of a suitable concentration on a polymer base film to form a polyvinyl alcohol film, and then in a closed environment, a cross-linking agent solution of a specific mass concentration is allowed to diffuse in the gas phase, and contact with the polyvinyl alcohol film, and a cross-linking reaction is performed to obtain a selective surface layer with high gas barrier capacity, thereby improving the gas barrier property of the resulting composite polymer membrane. In particular, the present invention achieves the diffusion of the cross-linking agent therein, the gas phase concentration of the cross-linking agent, the contact of the cross-linking agent with the polyvinyl alcohol film, and the occurrence of the cross-linking reaction by strictly controlling the temperature value relationship between the closed environment and the boiling point of the cross-linking agent. Compared with the commonly used method in the art, that is, mixing polyvinyl alcohol with the corresponding cross-linking agent into a uniform solution and then coating and cross-linking, the above method can provide a more refined control of the reaction process, so that the structure and performance of the modified layer obtained by cross-linking can be more effectively optimized, thereby improving the gas barrier property of the composite polymer membrane in which it is located without affecting other properties.

[0021] Specifically, the diffusion contact and cross-linking method can more accurately control the reaction depth and cross-linking degree. On the surface of the polyvinyl alcohol film, the cross-linking agent gradually diffuses, contacts and reacts, which helps to form a cross-linking structure similar to a gradient, so as to better cooperate with the polymer base film and ultimately optimize the gas barrier and conductivity of the resulting diaphragm. If the polyvinyl alcohol and the cross-linking agent are mixed into a whole solution and then cross-linked, the cross-linking reaction will be carried out simultaneously in the entire film layer system to be formed, so it is difficult to accurately control the depth and uniformity of the cross-linking, which is easy to cause excessive cross-linking or insufficient cross-linking of the internal structure, thereby affecting the performance of the composite diaphragm. From a thermodynamic point of view, diffusion contact and cross-linking can control the diffusion of the cross-linking agent, improve the thermodynamic stability of the reaction, and avoid reaction instability or material performance degradation caused by insufficient mixing or local overheating. The fully mixed slurry system may encounter problems such as local overheating or uneven reaction during the reaction, affecting the thermodynamic stability of the cross-linked product. Of course, in order to ensure the smooth progress of the above process, strictly controlling the mass concentration of the cross-linking agent to 0.1wt.%~10.0wt.%, is the key to optimizing the performance of the resulting modified layer and the reaction efficiency. A lower concentration may result in a slower crosslinking reaction rate, while a higher concentration may cause excessive crosslinking, resulting in a decrease in the porosity of the resulting modified layer material and a decrease in electrolyte transport performance. At the same time, the inventors have controlled the concentration of the crosslinking agent solution through a large number of experiments to form a thinner and more uniform crosslinked layer, thereby improving the gas barrier properties of the separator while maintaining good mechanical properties.

[0022] Furthermore, in order to more effectively achieve the diffusion of the crosslinking agent and its contact and crosslinking reaction with the polyvinyl alcohol film to form a modified layer with superior gas barrier properties and electrolyte transport properties, it is more preferred that the temperature difference between the closed environment and the boiling point of the crosslinking agent is 10°C to 35°C.

[0023] In general, the above-mentioned preparation method provided by the present invention combines ultrasonic spraying with in-situ diffusion and cross-linking to form an ultra-thin selective surface layer on the polymer base film, which significantly improves its gas barrier properties while maintaining good electrolyte transport performance and mechanical strength.

[0024] It should be supplemented that in step S4 of the preparation method provided by the present invention, the crosslinking agent solution in the closed environment is in excess of the polyvinyl alcohol film to ensure that the crosslinking agent can diffuse and fill the closed environment, thereby ensuring that it can contact the polyvinyl alcohol film and undergo a crosslinking reaction.

[0025] In several typical embodiments, the mass concentration of the polyvinyl alcohol solution in step S1 is 0.1wt.% to 0.5wt.%, so that during ultrasonic spraying, smaller and more uniform droplets are formed, and then a more uniform thin layer is formed on the surface of the polymer base film, which is conducive to controlling the thickness and pore structure of the modified layer obtained by subsequent cross-linking, and improving its gas barrier properties. Preferably, the mass concentration of the cross-linking agent solution in step S3 is 0.5wt.% to 2.5wt.%, which can better control its diffusion and the cross-linking reaction with the polyvinyl alcohol film, forming a modified layer with a more uniform structure and higher gas barrier properties.

[0026] In order to more accurately control the thickness of the polyvinyl alcohol wet film obtained by spraying, so as to obtain a modified layer with higher gas barrier properties after cross-linking, it is preferred that in step S2, the number of spraying cycles of ultrasonic spraying is 0 to 1000 times, and more preferably 50 to 200 times. In several more typical embodiments, the ultrasonic spraying speed of ultrasonic spraying is 0.1 mL / h to 2 mL / h, more preferably 0.5 mL / h to 1.0 mL / h, and the nozzle moving speed is 10 mm / s to 500 mm / s, and more preferably 50 mm / s to 100 mm / s. In order to form ultrasonic droplets of a more suitable size, and to make the resulting fine droplets contact with the polymer base film, to form a more uniform and dense polyvinyl alcohol film, and ultimately improve the gas barrier properties, electrolyte transport performance and mechanical stability of the diaphragm.

[0027] Furthermore, in order to allow the polyvinyl alcohol wet film obtained by ultrasonic spraying to dry at a more suitable speed, form a stable structure, and suppress the possibility of structural damage caused by excessive temperature, the drying temperature in step S2 is preferably 30° C. to 120° C. When the drying temperature in step S2 is more preferably 50° C. to 100° C., a denser and more stable polyvinyl alcohol film can be formed, so that a modified layer with a more stable microstructure can be formed when it is subsequently contacted and cross-linked with a cross-linking agent, and its gas barrier properties and mechanical strength are higher, and the bonding force with the polymer base film is also stronger.

[0028] In several typical embodiments, the crosslinking agent is selected from one or more of glutaraldehyde, glyoxal, formaldehyde, boric acid, dimethylol urea and trimethylol melamine, preferably glyoxal. The above preferred crosslinking agent types (especially glutaraldehyde, glyoxal and formaldehyde) can form more stable crosslinking bonds with the hydroxyl groups in PVA, thereby forming a high-density crosslinking network, thereby improving the gas barrier properties and mechanical stability of the obtained modified layer.

[0029] Furthermore, the temperature of the closed environment in step S4 is preferably 50°C to 90°C, preferably 60°C to 80°C. The temperature range of 50°C to 90°C can more effectively promote the diffusion and contact between the crosslinking agent and the PVA molecules on the surface or inside the PVA film, thereby accelerating the crosslinking reaction. At the same time, it also promotes the crosslinked membrane structure to exhibit higher stability. Avoid excessively high temperatures that may cause structural instability of the PVA film and the resulting crosslinked layer, causing thermal degradation or pore size changes, affecting the performance of the diaphragm. The crosslinking reaction in the temperature range of 60°C to 80°C, which is more preferred in the present invention, can form a more stable and dense crosslinked layer, which exhibits higher gas barrier properties and mechanical stability.

[0030] When the PVA and the cross-linking agent are in contact and cross-linked in a closed environment, in addition to the above-mentioned control of temperature, the present invention also comprehensively considers the influence of humidity to obtain a modified layer with a denser microstructure and better gas barrier properties. Among them, because PVA is a hydrophilic polymer, the increase in humidity can promote the swelling of PVA molecules and increase the contact area between them and the cross-linking agent molecules. In an environment with too high humidity, excessive swelling of PVA may cause the destruction of the membrane structure obtained by cross-linking, affecting its performance. Therefore, after a large number of experiments, the inventors prefer the humidity of the closed environment to be 20% RH to 70% RH. The above-mentioned control of the environmental humidity can synergistically promote the effective contact and cross-linking reaction between PVA and the cross-linking agent, while better avoiding the adverse effects that moisture may have on the diaphragm, and ultimately forming a composite polymer diaphragm with better comprehensive performance.

[0031] In order to allow the contact and cross-linking reaction between PVA and the cross-linking agent to proceed fully, to form a more stable modified layer, and to improve the overall gas barrier properties, electrolyte transport properties and alkali resistance of the composite diaphragm, the time for the diffusion and cross-linking reaction in step S4 is preferably 2h to 48h, more preferably 12h to 24h.

[0032] In several typical embodiments, the polymer base membrane is selected from one or more of polyphenylene sulfide membrane, polytetrafluoroethylene membrane, polypropylene membrane and polysulfone membrane. Compared with other porous polymer base membranes commonly used in the art, the above polymer base membrane has better chemical stability and mechanical strength, can provide stable support, and has stronger bonding with the polyvinyl alcohol membrane and the modified layer formed by subsequent cross-linking, and the overall mechanical properties are more stable.

[0033] The second aspect of the present invention provides a composite polymer membrane, which is prepared by the preparation method of the above-mentioned composite polymer membrane; the composite polymer membrane includes a polymer base membrane and a modified layer arranged on the surface of at least one side of the polymer base membrane, and: the thickness of the polymer base membrane is 50μm to 600μm; and / or the thickness of the modified layer is 100nm to 8μm. The composite polymer membrane prepared by the above-mentioned method provided by the present invention has a polymer base membrane with high mechanical strength and a modified layer formed by polyvinyl alcohol and a cross-linking agent with high gas barrier properties, so the composite membrane not only has excellent electrolyte transport performance and mechanical strength, but also exhibits excellent gas barrier properties. At the same time, the provision of the modified layer not only improves the gas barrier properties of the membrane, but also further enhances its mechanical strength and improves its alkali resistance. In particular, compared with a larger density range, the thickness of the modified layer in the composite polymer membrane obtained by the present invention is 100nm~8μm, which can more effectively improve the gas barrier properties and protect the mass transfer effect, while also improving the bonding strength with the polymer base membrane and enhancing the overall mechanical strength and service life of the composite membrane.

[0034] The third aspect of the present invention provides an application of the above-mentioned composite polymer membrane as an electrolyzer membrane material in the field of hydrogen production by alkaline water electrolysis. The composite polymer membrane obtained by the present invention has good gas barrier properties, chemical stability and mechanical strength, which can not only significantly improve the efficiency of hydrogen production by water electrolysis, but also extend the service life of the membrane and reduce maintenance costs. The thinner modified layer means that the electrolyte has less resistance when passing through the composite membrane, thereby improving the current density and electrolysis efficiency of the alkaline electrolyzer in which it is located. In particular, the composite membrane with the above-mentioned thinner modified layer can better optimize the mass transfer performance of hydroxide ions (OH-) and gases (such as hydrogen and oxygen) in the electrolyte in which it is located, ensuring that ion transport and gas separation in the water electrolysis process are more efficient.

[0035] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.

[0036] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.

[0037] Example 1

[0038] A method for preparing a composite polymer diaphragm:

[0039] (1) preparing linear polyvinyl alcohol (PVA) into a PVA aqueous solution with a mass concentration of 0.1 wt.%;

[0040] (2) Using a 600 μm thick polyphenylene sulfide (PPS) membrane (purchased from Japan, Toray) as a base membrane, the PVA aqueous solution was sprayed on one side of the PPS membrane by ultrasonic spraying to form a polyvinyl alcohol wet film. During ultrasonic spraying, the spray speed was set to 1 mL / h, the nozzle moving speed was 100 mm / s, and the number of spray cycles was set to 200 times. The PPS base membrane loaded with the polyvinyl alcohol wet film was then dried at 80°C to obtain a polymer base membrane loaded with a polyvinyl alcohol film;

[0041] (3) preparing glyoxal (whose boiling point is 48.6° C.) into a cross-linking agent solution with a mass concentration of 1.5 wt.%;

[0042] (4) placing a large amount of excess crosslinking agent solution and the polymer base film loaded with polyvinyl alcohol film in a closed reactor, and after 24 hours of diffusion and crosslinking reaction, the evaporated crosslinking agent and the PVA film undergo crosslinking reaction to form a modified layer with a thickness of 5 μm. The temperature in the closed reactor is 60°C (the difference between this temperature and the boiling point of the crosslinking agent is 11.4°C), and the humidity is 50% RH;

[0043] (5) The composite membrane obtained in step (4) is washed three times with deionized water to remove the residual cross-linking agent, and finally a composite polymer membrane is obtained.

[0044] Example 2

[0045] A method for preparing a composite polymer diaphragm:

[0046] (1) preparing linear polyvinyl alcohol (PVA) into a PVA aqueous solution with a mass concentration of 0.3 wt%;

[0047] (2) Using a 300 μm thick polytetrafluoroethylene (PVDF) membrane (purchased from BASF) as a base membrane, the above-mentioned PVA aqueous solution was sprayed on one side of the PPS membrane by ultrasonic spraying to form a polyvinyl alcohol wet film. During ultrasonic spraying, the ultrasonic spray speed was set to 0.5 mL / h, the nozzle moving speed was 50 mm / s, and the number of cycle spraying was set to 100 times. Thereafter, the PPS base membrane loaded with the polyvinyl alcohol wet film was dried at 50°C to obtain a polymer base membrane loaded with a polyvinyl alcohol film;

[0048] (3) preparing glyoxal into a cross-linking agent solution with a mass concentration of 0.5 wt %;

[0049] (4) placing a large amount of excess crosslinking agent solution and the polymer base film loaded with polyvinyl alcohol film in a closed reactor, and after 12 hours of diffusion and crosslinking reaction, the evaporated crosslinking agent and the PVA film undergo crosslinking reaction to form a modified layer with a thickness of 1 μm. The temperature in the closed reactor is 80°C (the difference between this temperature and the boiling point of the crosslinking agent is 31.4°C), and the humidity is 40% RH;

[0050] (5) The composite membrane obtained in step (4) is washed three times with deionized water to remove the residual cross-linking agent, and finally a composite polymer membrane is obtained.

[0051] Example 3

[0052] A method for preparing a composite polymer diaphragm:

[0053] (1) preparing linear polyvinyl alcohol (PVA) into a PVA aqueous solution with a mass concentration of 0.5 wt%;

[0054] (2) Using a 200 μm thick polysulfone (PSF) membrane (purchased from BASF) as a base membrane, the PVA aqueous solution was sprayed on one side of the PS membrane by ultrasonic spraying to form a polyvinyl alcohol wet film. During ultrasonic spraying, the ultrasonic spraying speed was set to 0.2 ml / h, the nozzle moving speed was 50 mm / s, and the number of spray cycles was set to 50 times. The PSF base membrane loaded with the polyvinyl alcohol wet film was then dried at 50°C to obtain a polymer base membrane loaded with a polyvinyl alcohol film;

[0055] (3) preparing glyoxal into a cross-linking agent solution with a mass concentration of 2.5 wt %;

[0056] (4) placing a large amount of excess crosslinking agent solution and the polymer base film loaded with polyvinyl alcohol film in a closed reactor, and after 12 hours of diffusion and crosslinking reaction, the evaporated crosslinking agent and the PVA film undergo crosslinking reaction to form a modified layer with a thickness of 0.5 μm. The temperature in the closed reactor is 60° C. (the difference between this temperature and the boiling point of the crosslinking agent is 11.4° C.), and the humidity is 60% RH;

[0057] (5) The composite membrane obtained in step (4) is washed three times with deionized water to remove the residual cross-linking agent, and finally a composite polymer membrane is obtained.

[0058] Example 4

[0059] A method for preparing a composite polymer diaphragm:

[0060] The only difference between this embodiment and embodiment 1 is that the mass concentration of the PVA aqueous solution in step (1) is changed to 0.08 wt.%; and the mass concentration of the cross-linking agent solution in step (3) is changed to 0.4 wt.%.

[0061] Example 5

[0062] A method for preparing a composite polymer diaphragm:

[0063] The only difference between this embodiment and embodiment 1 is that the mass concentration of the PVA aqueous solution in step (1) is changed to 1 wt.%; and the mass concentration of the cross-linking agent solution in step (3) is changed to 3 wt.%.

[0064] Example 6

[0065] A method for preparing a composite polymer diaphragm:

[0066] The difference between this embodiment and embodiment 1 is only in the parameter setting of ultrasonic spraying in step (2), specifically: the ultrasonic spraying speed is 0.1 mL / h, the nozzle moving speed is 10 mm / s, and the number of cycle spraying is set to 20 times.

[0067] Example 7

[0068] A method for preparing a composite polymer diaphragm:

[0069] The difference between this embodiment and embodiment 1 is only in the parameter setting of ultrasonic spraying in step (2), specifically: the ultrasonic spraying speed is 2 mL / h, the nozzle moving speed is 500 mm / s, and the number of cycle spraying is set to 300 times.

[0070] Example 8

[0071] A method for preparing a composite polymer diaphragm:

[0072] The only difference between this embodiment and embodiment 1 is that the drying temperature in step (2) is changed to 30°C.

[0073] Example 9

[0074] A method for preparing a composite polymer diaphragm:

[0075] The only difference between this embodiment and embodiment 1 is that the drying temperature in step (2) is changed to 120°C.

[0076] Example 10

[0077] A method for preparing a composite polymer diaphragm:

[0078] The difference between this embodiment and embodiment 1 is only the parameter setting of the closed reactor in step (4), specifically: the temperature in the closed reactor is 50° C. (the difference between this temperature and the boiling point of the cross-linking agent is 1.4° C.), and the humidity is 10% RH.

[0079] Embodiment 11

[0080] A method for preparing a composite polymer diaphragm:

[0081] The difference between this embodiment and embodiment 1 is only the parameter setting of the closed reactor in step (4), specifically: the temperature in the closed reactor is 90° C. (the difference between this temperature and the boiling point of the cross-linking agent is 41.4° C.), and the humidity is 80% RH.

[0082] Example 12

[0083] A method for preparing a composite polymer diaphragm:

[0084] The only difference between this embodiment and embodiment 1 is that the time for the diffusion and cross-linking reaction in step (4) is changed to 2 hours.

[0085] Comparative Example 1

[0086] A method for preparing a composite polymer diaphragm:

[0087] The difference between this comparative example and Example 1 is that the mass concentration of the PVA aqueous solution in step (1) is changed to 8 wt.%; and the mass concentration of the cross-linking agent solution in step (3) is changed to 12 wt.%.

[0088] Comparative Example 2

[0089] A method for preparing a composite polymer diaphragm:

[0090] The difference between this comparative example and Example 1 is that the mass concentration of the PVA aqueous solution in step (1) is changed to 0.005 wt.%; and the mass concentration of the cross-linking agent solution in step (3) is changed to 0.5 wt.%.

[0091] Comparative Example 3

[0092] A method for preparing a composite polymer diaphragm:

[0093] The only difference between this comparative example and Example 1 is that the temperature in the closed reactor in step (4) is changed to 40° C. (the difference between this temperature and the boiling point of the cross-linking agent is −8.6° C.).

[0094] Comparative Example 4

[0095] A method for preparing a composite polymer diaphragm:

[0096] The only difference between this comparative example and Example 1 is that the temperature in the closed reactor in step (4) is changed to 100° C. (the difference between this temperature and the boiling point of the cross-linking agent is 51.4° C.).

[0097] Comparative Example 5

[0098] A method for preparing a composite polymer diaphragm:

[0099] (1) mixing the PVA aqueous solution with a mass concentration of 0.1 wt. % obtained in Example 1 with the cross-linking agent solution with a mass concentration of 1.5 wt. % in a mass ratio of polyvinyl alcohol to glyoxal of 10:1 to obtain a mixed solution;

[0100] (2) The obtained mixed solution is cast on the surface of the PPS diaphragm used in Example 1 to form a film, and then placed in a closed reactor to undergo diffusion and cross-linking reactions under the conditions in Example 1 to obtain a modified layer.

[0101] Test Method

[0102] Bubble point pressure: Indicates the minimum gas pressure at which gas penetrates the diaphragm material and produces the first string of bubbles, measured according to GB / T32361-2015.

[0103] Surface resistance: It refers to the resistance of the diaphragm material to the transfer of electrolyte per unit area.

[0104] Tensile strength: measured according to GB1040.3-2006.

[0105] The above performance tests were performed on the membrane material samples obtained in each embodiment and comparative example, and the obtained results are shown in Table 1.

[0106] Table 1

[0107]

[0108]

[0109] From the above description, it can be seen that the above embodiments of the present invention prepare composite polymer separators with excellent gas barrier properties, electrolyte transport properties and mechanical properties. Especially embodiment 3 has a thinner thickness and also exhibits the best comprehensive performance, showing higher gas barrier properties, smaller surface resistance and higher tensile strength than other embodiments.

[0110] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.

[0111] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a composite polymer diaphragm, characterized in that: include: Step S1, preparing polyvinyl alcohol into a polyvinyl alcohol solution with a mass concentration of 0.01wt.% to 5.00wt.%; Step S2, spraying the polyvinyl alcohol solution onto one side of the polymer base film by ultrasonic spraying, and obtaining a polymer base film loaded with a polyvinyl alcohol film after drying; Step S3, preparing a cross-linking agent into a cross-linking agent solution with a mass concentration of 0.1wt.% to 10.0wt.%; Step S4, placing the crosslinking agent solution and the polymer base film loaded with the polyvinyl alcohol film in a closed environment, so that the crosslinking agent diffuses and contacts with the polyvinyl alcohol film; Through a cross-linking reaction, the cross-linking agent and the polyvinyl alcohol film form a modified layer, thereby obtaining the composite polymer diaphragm; The temperature of the sealed environment is higher than the boiling point of the cross-linking agent, and the difference between the temperature of the sealed environment and the boiling point of the cross-linking agent is 1° C. to 100° C.

2. The method for preparing a composite polymer membrane according to claim 1, characterized in that: In step S1, the mass concentration of the polyvinyl alcohol solution is 0.1wt.% to 0.5wt.%; and / or, In step S3, the mass concentration of the cross-linking agent solution is 0.5wt.% to 2.5wt.%.

3. The method for preparing a composite polymer membrane according to claim 1 or 2, characterized in that: In step S2, the number of spraying cycles of the ultrasonic spraying is 0 to 1000 times, preferably 50 to 200 times; More preferably, the ultrasonic spraying speed of the ultrasonic spraying is 0.1 mL / h to 2 mL / h, and the nozzle moving speed is 10 mm / s to 500 mm / s.

4. The method for preparing a composite polymer membrane according to claim 1 or 2, characterized in that: In step S2, the drying temperature is 30°C to 120°C, preferably 50°C to 100°C.

5. The method for preparing a composite polymer diaphragm according to any one of claims 1 to 4, characterized in that: The cross-linking agent is selected from one or more of glutaraldehyde, glyoxal, formaldehyde, boric acid, dimethylol urea and trimethylol melamine, preferably glyoxal.

6. The method for preparing a composite polymer membrane according to any one of claims 1 to 5, characterized in that: In step S4, the temperature of the closed environment is 50°C to 90°C, preferably 60°C to 80°C; Preferably, the humidity of the closed environment is 20% RH to 70% RH.

7. The method for preparing a composite polymer diaphragm according to any one of claims 1 to 6, characterized in that: In step S4, the diffusion and cross-linking reaction time is 2 h to 48 h, preferably 12 h to 24 h.

8. The method for preparing a composite polymer diaphragm according to any one of claims 1 to 7, characterized in that: The polymer-based membrane is selected from one or more of a polyphenylene sulfide membrane, a polytetrafluoroethylene membrane, a polypropylene membrane and a polysulfone membrane.

9. A composite polymer diaphragm, characterized in that: The composite polymer membrane is prepared by the method for preparing a composite polymer membrane according to any one of claims 1 to 8; the composite polymer membrane comprises the polymer base membrane and a modified layer disposed on at least one side of the surface of the polymer base membrane, and: The polymer base film has a thickness of 50 μm to 600 μm; and / or the modified layer has a thickness of 100 nm to 8 μm.

10. Use of the composite polymer membrane according to claim 9 as an electrolytic cell membrane material in the field of hydrogen production by alkaline water electrolysis.